2011
DOI: 10.1016/j.bbr.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Threshold of adulthood for the onset of nicotine self-administration in male and female rats

Abstract: The great majority of tobacco addiction begins during adolescence. More heavily addicted smokers begin smoking earlier, but differentiating the neurobehavioral impact of nicotine self-administration during adolescence from self-selection bias (whereby people more prone to heavy addiction also begin earlier) cannot be ethically unconfounded in humans. The goals of this research were to determine the age threshold for the adult-like nicotine self-administration and determine sex differences. Male and female Spra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 61 publications
(61 reference statements)
4
44
1
Order By: Relevance
“…Rats exposed to experimenter-administered nicotine during early adolescence (P28-31) were found to subsequently exhibit increased cocaine self-administration, an effect not evident with exposure later in adolescence (P38-41) or in adulthood (P86-89)(Dao et al, 2011). In contrast, adolescent-onset nicotine self-administration was not observed to alter later cocaine self-administration, although females allowed to self-administer nicotine from 4-8 weeks of age self-administered more nicotine after a week of abstinence than females given the opportunity to self-administer nicotine from 8-12 weeks of age; this effect was not evident in males (Levin et al, 2011). In mice, nicotine exposure during early adolescence (P24-35) was reported to increase later oral self-administration and stimulant effects of nicotine relative to control animals, whereas mid- and late-adolescent exposures (P37-48; P50-61) did not (Adriani et al, 2002).…”
Section: Animal Studiesmentioning
confidence: 76%
“…Rats exposed to experimenter-administered nicotine during early adolescence (P28-31) were found to subsequently exhibit increased cocaine self-administration, an effect not evident with exposure later in adolescence (P38-41) or in adulthood (P86-89)(Dao et al, 2011). In contrast, adolescent-onset nicotine self-administration was not observed to alter later cocaine self-administration, although females allowed to self-administer nicotine from 4-8 weeks of age self-administered more nicotine after a week of abstinence than females given the opportunity to self-administer nicotine from 8-12 weeks of age; this effect was not evident in males (Levin et al, 2011). In mice, nicotine exposure during early adolescence (P24-35) was reported to increase later oral self-administration and stimulant effects of nicotine relative to control animals, whereas mid- and late-adolescent exposures (P37-48; P50-61) did not (Adriani et al, 2002).…”
Section: Animal Studiesmentioning
confidence: 76%
“…Studies of sex differences in drug-self administration in rodents are more abundant and consistent in the finding that females acquire self-administration faster, escalate use more during extended access and will work harder under a progressive ratio to obtain psychostimulants, nicotine, opioids and tetrahydrocannabinol (Anker & Carroll, 2011; Becker & Hu, 2008; Carroll & Anker, 2010; Carroll et al, 2004; Fattore et al, 2008; Fattore et al, 2009; Feltenstein, Ghee, & See, 2012; Levin et al, 2011; Lynch, 2006; Lynch et al, 2002). Most rodent studies have detected robust sex differences in alcohol consumption (females consume more, especially in mice) although the greater fluid consumption by females must be considered in evaluating reported results.…”
Section: Sex Differences In Drug Use In Animal Modelsmentioning
confidence: 97%
“…Research on the differential effects of nicotine in adolescents compared with adults is mixed. Several studies suggest that adolescent rats self-administer more nicotine (30 µg/kg) and acquire stable behavior faster than adults Levin, Rezvani, Montoya, Rose, & Swartzwelder, 2003;Levin et al, 2011). However, relatively little attention has been given to acquisition of self-administration at low doses.…”
Section: Model Considerationsmentioning
confidence: 99%
“…These data are limited, however, both in terms of the age of initiation and the exclusive focus on males. Several studies have reported sex differences in the acquisition of nicotine self-administration during adolescence Levin et al, 2011), including a greater likelihood of females acquiring at a low dose (5 µg/kg; Lynch, 2009). Likewise, other work has suggested that adolescents may be more sensitive to the potentiating effects of acetaldehyde (a tobacco constituent discussed in the Could Other Constituents of Tobacco Impact the Threshold for Self-administration?…”
Section: Model Considerationsmentioning
confidence: 99%